China - Sri Lanka Relations And Its Implications For India; The Period Of 2005-2015 - Ganeshalingam, K.T. (Faculty of Arts, University of Jaffna, Sri Lanka Collaboration with Association of Third World Studies - South Asia Chapter, 2017)
The China - Sri Lanka relationship is proceeding in a positive direction. Partic-ularly under the rule of President Mahinda Rajapaksa the political, economic, and military co-operation has been intensified. At the regional as well as international level both countries have established very close diplomatic ties. This has led to the growth of the dominance of China at a regional level and consequently it has been included in the group of countries competing for control of the Indian Ocean, giving China enhanced power to exercise authority in the region. Though both countries are neighbors, the Indo - China war in 1962 deepened and consolidated the enmity and contradictions between the two countries. China is a South East Asian country without any direct link to the Indian Ocean and therefore India observes the activities of China with ever increasing concern. We It can see that China is making a relentless effort to establish close ties with neighboring countries of India and trying to emerge as a global superpower . Meanwhile, India on the other hand, based on the economic progress and its close relationship with US, is making headway in becoming a global super power by 2020. According to marine research scholars, the oceans will play a vital role in deciding the destiny of global super powers.
Keywords: Diplomatic ties; Dominance; Neighbor Countries; Global